FACTORS ASSOCIATED WITH ANXIETY AMONG PREGNANT WOMEN : AN EARLY MENTAL HEALTH SCREENING STRATEGY - Eka Ratnasari; Nurhasanah Nurhasanah; Nunung Nurjanah; Nur Aliah; Pesona Riyanti; Nurhadia Kastani (Jurnal Kebidanan Khatulistiwa, 2026)
Background: Pregnancy is a period during which women experience substantial physical and psychological changes that may increase their vulnerability to mental health problems, particularly anxiety. The World Health Organization (WHO) estimates that approximately 10% of pregnant women experience anxiety during pregnancy, with the prevalence increasing to nearly 20% as childbirth approaches. Several factors, including maternal age, pregnancy experience, gestational age, educational level, income, and family support, may contribute to anxiety during pregnancy. This study aimed to identify factors associated with anxiety among pregnant women attending Arsy Medika Clinic, Cirebon Regency, West Java, Indonesia. Methods: A quantitative study with a cross-sectional design was conducted among pregnant women receiving antenatal care at Arsy Medika Clinic. Participants were recruited using an accidental sampling technique, resulting in a total of 35 respondents who met the inclusion and exclusion criteria. Anxiety was assessed using the Perinatal Anxiety Screening Scale (PASS) questionnaire. Data were analyzed using descriptive statistics and the Chi-square test to determine the association between maternal characteristics and anxiety. Results: Family income (p = 0.033) and family support (p = 0.009) were significantly associated with anxiety among pregnant women. In contrast, maternal age (p = 0.056), educational level (p = 0.892), employment status (p = 0.832), parity (p = 0.190), and gestational age (p = 0.913) were not significantly associated with anxiety. Conclusion: Family income and family support were the main factors associated with anxiety among pregnant women. These findings highlight the importance of incorporating routine mental health screening into antenatal care services, with particular attention to pregnant women experiencing socioeconomic challenges and inadequate family support. Strengthening early anxiety screening programs may facilitate timely identification and intervention to improve maternal mental health outcomes.